Technology As A Product Of Science Based On Philosophy - Muhammad Choerul Umam; Siti Masitoh; Mochamad Nursalim (FALASIFA : Jurnal Studi Keislaman, 2022)
Man defines science and philosophy as a genuine endeavor to comprehend a discipline's approach and notion. The periods' and developments' high needs have ushered philosophy into an arrangement by demonstrating how the "Mother of Science" develops effectively from each subject. Of course, being a human person, he will never be pleased with knowledge alone, but rather with knowledge and truth. Because truth is the state of something according to the real object, learning something through knowledge (philosophy) is a method of gaining objective and right knowledge. Furthermore, the job of philosophy in this context is to analyze and research human life from many perspectives. The goal of this research is to look at philosophy as the foundation for the development of scientific products in the form of technology, the function of which is to decide the path of human life itself. The job of technology is not only to solve issues encountered by humanity in certain locations and eras, but also to address many metaphysical concerns. The existence of philosophy and science is very necessary in the midst of the development of science and technology; its presence is demonstrated by the specialization of science, because scientists are expected to be able to realize their limitations by studying philosophy in order to avoid being trapped in an attitude of intellectual arrogance. The community is heterogeneous in this century, so the advancement of technology will produce complex difficulties and can transform the mindset of human life to a more sophisticated life pattern with technical power such as robots and the internet. Philosophy underpins science, which is employed as an axiological milestone in positively directing and controlling the development of science and technology for the benefit of mankind and the environment.